Homozygous GLUL deletion is embryonically viable and leads to glutamine synthetase deficiency. Issue 6 (1st October 2020) - Roifman, Maian; Niles, Kirsten M.; MacNeil, Lauren; Blaser, Susan; Noor, Abdul; Godoy, Ruth; van Mieghem, Tim; Ryan, Greg; Seaward, Gareth; Sondheimer, Neal; Mercimek‐Andrews, Saadet; Schulze, Andreas; et al.
Abstract: Glutamine synthetase (GS) is the enzyme responsible for the biosynthesis of glutamine, providing the only source of endogenous glutamine necessary for several critical metabolic and developmental pathways. GS deficiency, caused by pathogenic variants in the glutamate‐ammonia ligase ( GLUL) gene, is a rare autosomal recessive inborn error of metabolism characterized by systemic glutamine deficiency, persistent moderate hyperammonemia, and clinically devastating seizures and multi‐organ failure shortly after birth. The four cases reported thus far were caused by homozygous GLUL missense variants. We report a case of GS deficiency caused by homozygous GLUL gene deletion, diagnosed prenatally and likely representing the most severe end of the spectrum. We expand the known phenotype of this rare condition with novel dysmorphic, radiographic and neuropathologic features identified on post‐mortem examination. The biallelic deletion identified in this case also included the RNASEL gene and was associated with immune dysfunction in the fetus. This case demonstrates that total absence of the GLUL gene in humans is viable beyond the embryonic period, despite the early embryonic lethality found in GLUL animal models. Abstract :